Energy Saving Measures and Simulation in the Library Building of University of Surabaya - Elieser Tarigan (Politeknik Sukabumi, 2018)
The rapid rate use of fossil fuels globally results in many environmental problems. The adoption of energy efficient technology has the potential to substantially reduce the amount of energy used in buildings. This paper discuses the energy saving measures and simulation for a six-floor library building, University of Surabaya, Indonesia. Simulation was carried out using the Excellence in Design for Greater Efficiency (EDGE) simulation software. The results of simulation showed that 53% of energy efficiency can be reached, without lowering of the building comfort, by applying of four measures at the same time are daylight photoelectric sensors for internal spaces (OFE29), radiant cooling and heating system (OFE16), higher thermal performance glass (OFE8), and external shading devices (OFE4). The implementation of the four measures would result in reduction of 758 ton of CO2/year with a payback period of 2.2 years.